THE IMPORTANCE OF CASE TECHNOLOGY IN PRACTICAL ENGLISH CLASSES IN NON-PHILOLOGICAL EDUCATIONAL INSTITUTIONS - Tohirova, Shohsanam (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This article represents the teaching English for Specific Purposes (ESP) using case study technology. The importance of case study technology in teaching the English language in non-philological institutions and the benefits of this approach to language learning students is the main ideas that are included in this article.